Colonic phytobezoar - Kfouri,Cláudio Franco do Amaral (2018)
ABSTRACT Bezoars, although rare, represent a small part of the etiologies of intestinal obstructions. They are indigestible masses formed in human beings consisting of hair, seeds, plant fibers, fruits, and even medications. The present report concerns a male patient with a complaint of interrupted flatus passage and feces elimination and pain in the left iliac fossa, initially suspected as a neoplasia of the sigmoid colon. However, analysis of the surgical specimen revealed that the condition was characterized by intestinal obstruction due to an encapsulated phytobezoar. This fact demonstrates the importance of a differential diagnosis, with emphasis on the relevance of considering the presence of bezoars despite their rare occurrence.